Police work on domestic violence: impacts on the police officers: O trabalho policial na violência doméstica: impactos nos polícias (Brazilian Journal of Police Sciences, 2024)
AbstractIn Portugal, domestic violence (DV) is currently one of the main types of criminality recorded by the police forces and it is not a recent phenomenon. According to the Annual Internal Security Report 2021, there was a total of 26,520 reports of DV in 2021. All protection services and professionals to victims of this type of crime (and others), in which police officers are included, are characterised by the systematic exposure to traumatic situations. The manifest or latent violence they usually face may result in problems at the level of physical and psychological health of police officers, making them potential secondary victims. These consequences were studied in a qualitative research of exploratory nature. We present the results of the content analysis of 14 semi-structured interviews conducted with police officers of the Portuguese Public Security Police who systematically work with victims of DV.Keywords: domestic violence; police officers; secondary victimisation; traumatic situations.
Keywords: domestic violence; Police officers; secondary victimisation; traumatic situations